The Portrayal of Africa and Africans in the Book of Psalms - Adamo, David Tuesday (Black Theology, 2021)
There are more than 20 references to Africa and Africans in the book of Psalms.Unfortunately, not much attention has been paid to this Psalmic portrayal of Africa and Africans. The book portrays Africa and Africans as enemies, and oppressors of ancient Israel, as an arena, and instrument of Yahweh’s salvation. They are instrument and recipient of Yahweh's judgment. The main reason for such frequent references to Africa and Africans in the book of the psalm is not only because they are familiar with Africans but they are highly respected and mighty in power. Their black skin colour also bring their respectable identity. (Isa 18:1-6). Psalm 68:31 has also been part of the slory of colonization, pan-Africaanism enslavement, civilizing mission, and self-liberation.
paid
Keywords: Africa; Bible; Israel; Old Testament; Psalms; africans